Inhibition of cell proliferation and migration through nucleobase-modified polyamidoamine-mediated p53 delivery - Han H (Dove Medical Press, 2018)
Haobo Han,1,2 Wenqi Chen,2 Jiebing Yang,2 Xiao Liang,2 Yudi Wang,2 Quanshun Li,2 Yan Yang,2 Kun Li1 1School of Nursing, 2Key Laboratory for Molecular Enzymology and Engineering of Ministry of Education, School of Life Sciences, Jilin University, Changchun, People’s Republic of China Introduction: The nucleobase 2-amino-6-chloropurine-modified polyamidoamine (AP-PAMAM) was used as a carrier for p53 gene delivery to achieve the antitumor effects. Methods and materials: The condensation of p53 plasmid was studied through gel retardation assay, and the transfection efficiency was evaluated through the transfection assay of pEGFP-N3 and pGL-3 plasmids. Using human cervical carcinoma cell line HeLa as a model, the inhibition of cell proliferation and migration was studied through flow cytometry, wound healing and Transwell migration assays, respectively. The p53 expression level was detected through quantitative polymerase chain reaction and Western blotting analyses. Results: The carrier could condense p53 plasmid into stable nanoparticles at N/P ratios of 2.0, and higher transfection efficiency than polyamidoamine (PAMAM) could be obtained at all the N/P ratios studied. AP-PAMAM-mediated p53 delivery could achieve stronger antiproliferative effect than PAMAM/p53. The antiproliferative effect was identified to be triggered by the induction of cell apoptosis (apoptotic ratio of 26.17%) and cell cycle arrest at S phase. Additionally, AP-PAMAM/p53 transfection has been found to suppress the cell migration and invasion of cancer cells. Finally, the enhanced p53 expression level could be detected after p53 transfection at mRNA and protein levels. Conclusion: The PAMAM derivative-mediated p53 delivery could be a promising strategy for achieving tumor gene therapy. Keywords: nucleobase, polyamidoamine, p53 delivery, cell proliferation, cell migration